2021
DOI: 10.3168/jds.2020-18894
|View full text |Cite
|
Sign up to set email alerts
|

Progressive inclusion of pearl millet herbage as a supplement for dairy cows fed mixed rations: Effects on methane emissions, dry matter intake, and milk production

Abstract: The inclusion of grazing in dairy feeding systems can improve animal welfare and reduce feed costs and labor for animal care and manure management. This work aimed to evaluate the effects of including pearl millet herbage (Pennisetum glaucum 'Campeiro') as a supplement for dairy cows fed total mixed rations (TMR). The treatments included 100% TMR offered ad libitum (control, TMR 100 ), 75% TMR ad libitum intake + access to grazing of a pearl millet pasture between the morning and afternoon milkings (7 h/d; pTM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Neither CH 4 yield (g/kg of DMI) nor CH 4 intensity (g/kg of ECM) changed ( P ≥ 0.23) in response management system ( Table 4 ). We detected a more pronounced reduction in CH 4 production (i.e., –19%) in grazing (mean = 368 g/d) versus confinement (mean = 453 g/d; data not shown) when using data from selected studies ( n = 4; O’Neill et al, 2011 ; Civiero et al, 2021 ; Brito et al, unpublished) whereby enteric CH 4 production was directly measured. Furthermore, CH 4 yield (–7.2%) and CH 4 intensity (–6.2%) were both lower in cows under grazing than confinement management in these 4 studies (data not shown).…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…Neither CH 4 yield (g/kg of DMI) nor CH 4 intensity (g/kg of ECM) changed ( P ≥ 0.23) in response management system ( Table 4 ). We detected a more pronounced reduction in CH 4 production (i.e., –19%) in grazing (mean = 368 g/d) versus confinement (mean = 453 g/d; data not shown) when using data from selected studies ( n = 4; O’Neill et al, 2011 ; Civiero et al, 2021 ; Brito et al, unpublished) whereby enteric CH 4 production was directly measured. Furthermore, CH 4 yield (–7.2%) and CH 4 intensity (–6.2%) were both lower in cows under grazing than confinement management in these 4 studies (data not shown).…”
Section: Resultsmentioning
confidence: 78%
“…Milk yield was 9.3% lower ( P < 0.01; Table 3 ) in grazing versus confined dairy cows likely in response to a 9.5% drop in DMI leading to decreased energy intake. In 3 studies used in the data set (i.e., Fajardo et al, 2015 ; Soutto et al, 2020 ; Civiero et al, 2021 ), grazing cows received less concentrate than those in confinement, while in 2 other experiments (i.e., Kolver and Mullen, 1998 ; O’Neill et al, 2011 ), herbage was not supplemented with concentrate (100% grazing; Table 1 ). Therefore, decreased or no concentrate supplementation also contributed to the milk yield reduction in grazing dairy cows ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… The data may be useful for researchers and nutritionists who study dairy cow nutrition at grazing in order to simulate and/or predict intake regulation of individual cows. Few published studies have investigated different strategies of maize silage supplementation of grazing dairy cows that combine supplementation level and herbage allowance or combine the timing of supplement distribution and the daily access time to pasture [ 1 , 2 , 3 ]. This study provides individual daily data on methane emissions estimated using the Laser Methane Detector [ 4 , 5 ].…”
Section: Value Of the Datamentioning
confidence: 99%